2006
DOI: 10.2337/diabetes.55.03.06.db05-1075
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the Adiponutrin Gene Influences Its Expression and Associates With Obesity

Abstract: Adiponutrin is one of three recently identified adipocyte lipases. Surprisingly, these proteins also retain transacylase activity, a hitherto unknown pathway of triacylglycerol synthesis in the adipocytes. This may enable them to participate in both anabolic and catabolic processes. The adiponutrin gene (ADPN) is downregulated by fasting and upregulated by refeeding, suggesting a role in lipogenesis. Experiments in human adipocytes confirmed that the gene is upregulated in response to insulin in a glucose-depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
81
3

Year Published

2006
2006
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(92 citation statements)
references
References 42 publications
8
81
3
Order By: Relevance
“…95,96 Obese subjects have been reported to have either increased or unchanged levels of abdominal adipose tissue ADPN mRNA levels. 95,97 Two ADPN intronic polymorphisms are associated with obesity. 97 Carriers of the obesity-associated variants display a lower increase in levels of adipose tissue ADPN mRNA and increased basal lipolysis compared to non-carriers.…”
Section: Pathways Controlling Lipid Storage In Adipocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…95,96 Obese subjects have been reported to have either increased or unchanged levels of abdominal adipose tissue ADPN mRNA levels. 95,97 Two ADPN intronic polymorphisms are associated with obesity. 97 Carriers of the obesity-associated variants display a lower increase in levels of adipose tissue ADPN mRNA and increased basal lipolysis compared to non-carriers.…”
Section: Pathways Controlling Lipid Storage In Adipocytesmentioning
confidence: 99%
“…95,97 Two ADPN intronic polymorphisms are associated with obesity. 97 Carriers of the obesity-associated variants display a lower increase in levels of adipose tissue ADPN mRNA and increased basal lipolysis compared to non-carriers. 97 Perilipin (PLIN) is a phosphoprotein that coats the surface of intracellular lipid droplets in adipocytes and protects them against hydrolysis.…”
Section: Pathways Controlling Lipid Storage In Adipocytesmentioning
confidence: 99%
“…Adiponutrin mRNA levels were determined in fed, fasted and re-fed animals, as both stimuli (fasting/re-feeding) produce important acute changes in adiponutrin expression. 2,[8][9][10] ATGL levels were only determined in fed and fasted animals because fasting is the most important stimulus affecting the expression of the ATGL gene, 7,18,19 while 3 or 12 h refeeding after fasting does not produce any change in the ATGL mRNA levels attained during fasting. 36,37 Total RNA was extracted using Tripure reagent (Roche, Barcelona, Spain) according to the instructions provided by the supplier.…”
Section: Real-time Quantitative Rt-polymerase Chain Reaction (Q-pcr) mentioning
confidence: 99%
“…[21][22][23] Adiponutrin and ATGL mRNA expression has been described to be altered in adipose tissue of animal models of genetic obesity, 2,7,10 and it has been demonstrated that two human adiponutrin polymorphisms are associated with obesity. 9,24 In addition, our group has reported that adiponutrin nutritional regulation is impaired in obese Zucker rats 10 and that fasting upregulation of ATGL in white adipose tissue is impaired in old rats, which could be related to the weight gain that occurs with aging. 19 However, the studies relating adiponutrin and ATGL expression with obesity have been carried out mainly using genetic models of obesity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation